Puzzle-assisted scramble model to improve elementary school students' science and social sciences learning outcomes - Rosmiati Rosmiati; Irman Syarif; Misran Misran (Arshaka: Social Sciences and Education, 2026)
This research aims to improve student learning outcomes through the application of the Scramble learning model assisted by puzzle media. This study uses the Classroom Action Research approach with the Kemmis and McTaggart models which is carried out in two cycles, including the stages of planning, implementation of actions, observation, and reflection. The research subjects were 18 students in class V of MI Muhammadiyah Kalosi. The data collection technique uses learning outcome tests, observation of teacher and student activities, and documentation. The data was analyzed using quantitative descriptive techniques. The results showed that the application of the Scramble learning model assisted by puzzle media was able to gradually increase students' learning outcomes in each cycle, with the percentage of learning completeness increasing from 33.33% in pre-action to 72.22% in Cycle I, and reaching 100% in Cycle II. The practical implications of this study show that the learning model can be used by teachers to increase involvement, motivation, collaboration, and understanding of science concepts as a whole, as well as become an effective strategy in designing more interactive and engaging learning in elementary schools.